Penerapan Manajemen Asuhan Keperawatan Profesional Sebagai Upaya Peningkatan Mutu Asuhan : Implementation of Professional Nursing Care Management as an Effort to Improve the Quality of Care - Tri Wahyuni, Nurlely; Wardani, Ratna (Jurnal Abdi Keperawatan dan Kedokteran, 2025)
Professional Nursing Care Management (PNCM) is a structured approach aimed at improving the quality of nursing services by emphasizing patient safety and professional standards. Despite its significance, many hospitals encounter barriers in implementing PNCM optimally due to uneven educational levels, limited nurse competencies, unsupportive management systems, and low staff motivation. These challenges can lead to suboptimal nurse performance and reduced care quality. This community-based project aimed to improve nursing care quality at Dayaku Raja Regional Public Hospital through the implementation of PNCM. A SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was conducted to identify internal and external factors affecting PNCM implementation. Based on the analysis, priority strategies were developed. Interventions included planning and organizing a care model, implementing care based on nursing standards, enhancing nurse competencies, promoting integrated documentation, and encouraging multidisciplinary collaboration. The effectiveness of implementation was evaluated using nursing quality indicators. The initial assessment led to the development and formalization of nursing care guidelines. Post-intervention evaluation showed improved compliance with nursing protocols such as standardized handovers and nursing conferences. There was a noticeable increase in patient satisfaction and quality indicators related to nursing services. The implementation of PNCM proved to be effective in enhancing nursing care quality. Strengthening nurse competencies, supporting organizational structures, and maintaining continuous quality evaluation are critical to sustaining improvements. The success at Dayaku Raja Hospital may serve as a model for similar healthcare facilities.